Replacing coal-fired power plants by photovoltaics in the Portuguese electricity system - Figueiredo, Raquel (2019)
The decarbonization of the Portuguese electricity system, currently around 50% renewable-based, is undergoing with the commitment to reach 60% of renewable electricity share by 2020. Because of this, the phase-out of the two remaining coal-fired power plants has been receiving close attention, as they currently contribute to about one-fifth of the total electricity generation and two-thirds of the CO2 emissions in the power sector. This work assesses the impact of eliminating coal-fired generation from the Portuguese electricity system without replacing it, and explores a cleaner supply alternative achievable before 2025. Coal phase-out without substitution results in slightly increased CO2 emissions for the atmosphere if one assumes that the required additional imports are of carbon-intensive electricity, leading to the need of adding clean power capacity to the system. It is shown that coal plants could be replaced by about 8 GW of photovoltaics if accompanied by a modest increase in the already existing hydro pump capacity. In this case, the renewable electricity share increases to 77%, and carbon footprint decreases by 56%